Analysis of Artificial Intelligence (AI) Technology Acceptance Among Accounting Employees: A Model Based on UTAUT-3 - Permatasari, Novia; Rahmawati, Mia Ika (E-Jurnal Akuntansi, 2025)
This study aims to analyze the factors that influence the acceptance and use of artificial intelligence (AI) technology by accounting employees using the UTAUT-3 model. Using a quantitative approach, data were collected from 162 accounting employees of an Internet Service Provider (ISP) company in East Java via a questionnaire and analyzed using PLS-SEM via SmartPLS 4. The results indicate that performance expectations, effort expectations, and social impact positively influence behavioral intention, while facility conditions, hedonic motivation, habit, and personal innovation do not have a significant effect. Habit influences actual usage behavior, but behavioral intention does not have a significant effect. These findings indicate the dominance of functional factors over pleasure or infrastructure in driving AI adoption. This study enriches the behavioral accounting literature and provides managerial implications for organizations in strategically adopting AI in financial reporting.